Plasma Cell–Free DNA Next-Generation Sequencing to Diagnose and Monitor Infections in Allogeneic Hematopoietic Stem Cell Transplant Patients. (16th November 2018) - Fung, Monica; Zompi, Simona; Seng, Hon; Hollemon, Desiree; Parham, Adama; Hong, David K; Bercovici, Sivan; Dolan, Estelle; Lien, Kathy; Teraoka, Justin; Logan, Aaron C; Chin-Hong, Peter
Abstract: Allogeneic hematopoietic stem cell transplant patients are at risk for common and atypical infections. Superior diagnostics can decrease infection-related morbidity and mortality. A novel plasma cell–free DNA next-generation sequencing test detected an uncommon presentation of Chlamydia trachomatis and recurrent and metastatic complications of Staphylococcus aureus bacteremia before standard microbiology.